WORKSHOP PENINGKATAN PEMBELAJARAN BERDEFERENSIASI BEBERBASIS KONTEN DI SDN SAMPANG AGUNG KABUPATEN MOJOKERTO - Danang Prastyo; Wahyu Susiloningsih; Dian Kusmaharti; Ida Sulistyawati; Achmad Fanani (Universitas PGRI Adi Buana Surabaya, 2024)
Differentiated learning in elementary schools (SD) is something that needs to be implemented by educational units. To realize good differentiated learning at the elementary school level, PGSD UNIPA Surabaya carried out a Workshop on Increasing Teacher Competency in Content-Based Differentiated Learning. This training population was carried out at SDN Kutorejo, Mojokerto Regency and the training sample was at SDN Sampang Agung Kutorejo, Mojokerto Regency. Data collection techniques use observation, documentation and filling out satisfaction questionnaires. The results of this training were that one hundred percent of participants were satisfied with the Workshop on Improving Teacher Competency in Content-Based Differentiated Learning, the participants' abilities increased from a score of 50 to 80.